2021
DOI: 10.1016/j.omtn.2021.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Biological roles and therapeutic potential of circular RNAs in osteoarthritis

Abstract: Osteoarthritis (OA) is a common and disabling joint disorder that is mainly characterized by cartilage degeneration and narrow joint spaces. The regulatory functions of non-coding RNAs (long non-coding RNAs, microRNAs [miRNAs], and circular RNAs [circRNAs]) in OA progression have attracted considerable attention, and the function of circular RNAs in the context of OA has been an increasingly popular research topic in the last 6 years. Recent studies have reported that various circRNAs can delay or aggravate di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 92 publications
0
27
1
Order By: Relevance
“…They are able to regulate gene expression by sponging RNA-binding proteins and miRNAs. Recent studies describe a series of functions of circRNAs in OA, including the modulation of metabolic homeostasis in cartilage matrix as well as their participation in inflammation, chondrocyte apoptosis, proliferation, and autophagy 26 , 27 . Examples of some recently discovered circRNAs as biomarkers in OA include the hsa_circ_0032132, which is significantly increased in the blood levels of patients with OA compared with healthy controls 28 , and the hsa_circ_0101873, hsa_circ_0104595, and hsa_circ_0101251, whose levels are significantly increased in the synovial fluid of patients with OA and even show a positive correlation with radiographic severity and WOMAC (Western Ontario and McMaster Universities Arthritis Index) score 29 .…”
Section: Other Small Non-coding Rnasmentioning
confidence: 99%
“…They are able to regulate gene expression by sponging RNA-binding proteins and miRNAs. Recent studies describe a series of functions of circRNAs in OA, including the modulation of metabolic homeostasis in cartilage matrix as well as their participation in inflammation, chondrocyte apoptosis, proliferation, and autophagy 26 , 27 . Examples of some recently discovered circRNAs as biomarkers in OA include the hsa_circ_0032132, which is significantly increased in the blood levels of patients with OA compared with healthy controls 28 , and the hsa_circ_0101873, hsa_circ_0104595, and hsa_circ_0101251, whose levels are significantly increased in the synovial fluid of patients with OA and even show a positive correlation with radiographic severity and WOMAC (Western Ontario and McMaster Universities Arthritis Index) score 29 .…”
Section: Other Small Non-coding Rnasmentioning
confidence: 99%
“…Circular RNAs (circRNAs) are noncoding RNA molecules characterized by covalent closed loops free of 3ʹ and 5ʹ ends [ 10 ]. An increasing number of researches have suggested that novel circRNAs play various roles in osteoarthritis progression [ 11 ], such as CircCDH13 [ 12 ], circCSNK1G1 [ 13 ], circ_0128846 [ 14 ], etc. Has_circ_0005567 was first reported as osteoarthritis-related circRNA [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the constant exploration for osteosarcoma pathogenesis, increasing number of circRNAs have been discovered and their functions attract more and more attention [ 16 , 17 ]. In terms of biogenesis, circRNAs were generated from certain gene via back-splicing, which is a special splicing manner [ 18 , 19 ]. Circular RNAs are a novel class of non-coding RNAs that are regulating more and more pathophysiological process in the regulation of osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%